Alleviation of Hepatic Steatosis: Dithizone-Related Gut Microbiome Restoration During Paneth Cell Dysfunction - Zhang, Saisai; Tun, Hein M.; Zhang, Dengwei; Chau, Hau-Tak; Huang, Fung-Yu; Kwok, Hin; Wong, Danny Ka-Ho; Mak, Lung-Yi; Yuen, Man-Fung; Seto, Wai-Kay (Frontiers in Microbiology, 2022)
Non-alcoholic fatty liver disease (NAFLD), the world’s most common chronic liver disease, is increasingly linked to gut dysbiosis. Paneth cell secretes antimicrobial peptides that regulate the gut microbiome, but its role in the pathogenesis of NAFLD remains unclear. Here, we determine the changes in NAFLD development and gut microbial composition and function via the injection of dithizone that can pharmacologically deplete the granules of Paneth cells. Eight-week-old C57BL/6J male mice (n=31) were given a high-fat diet (HFD) or standard control diet for 12 weeks. Dithizone (10 mg/kg) was intravenously injected every three weeks during the period of diet feeding. Metagenomic DNA was extracted from fecal samples for PacBio Single-Molecule Real-Time sequencing to identify changes in microbial composition and predicted function. We observed dithizone-treated HFD mice, when compared to non-treated HFD mice, to have significant reductions in hepatic triglyceride content (28.98 mg/g vs. 53.52 mg/g, p=0.0419); plasma insulin level (2.18 ng/mL vs. 6.63 ng/mL, p=0.0079); and relative mRNA levels of fatty acid synthase (0.52 vs. 1.57, p=0.0428) and stearoyl-CoA desaturase-1 (0.43 vs. 1.20, p=0.0121). Bacterial taxonomic profiling found dithizone-treated HFD mice, when compared to non-treated HFD mice, had a lower Firmicutes/Bacteroidetes ratio (2.53 vs. 5.26, p=0.0541); a higher relative abundance of Bacteroides ASV21 and ASV42 (1.04% vs. 0.22%, p=0.0277 and 0.96% vs. 0.09%, p=0.0213), and a reduction in microbes belonging to Firmicutes (all p<0.05). Bacteroides species correlated positively with predicted microbial functions as L-methionine (r=0.54, p=0.0019) and tetrahydrofolate (r=0.52, p=0.0029) biosynthesis. Collectively, dithizone treatment was associated with alleviation in the severity of liver steatosis in HFD-fed mice, possibly through gut microbiome modulation involving the increase in Bacteroides, suggesting microbiome targeted therapies may have a role in the treatment of NAFLD.